Síndrome de dolor miofascial - Vergara B., Loreto (Revista Hospital Clínico Universidad de Chile, 2018)
The myofascial pain syndrome is an entity that is often associated with many of the prevalent pathologies that generate musculoskeletal pain distributed in the different body segments (upper extremities, spine and lower extremities), and may be responsible for the chronification of problem if it is not considered, diagnosed and managed in a comprehensive and timely manner in conjunction with the underlying pathology.